Robust Feed-forward Schemes for Pitch Angle Control of Unmanned - Muhammad Salihin, Saealal (2010)
This paper presents investigations into the development of robust feed-forwards control schemes for pitch angle control of an unmanned underwater vehicle system. A linear model of unmanned underwater vehicle system is consider and the dynamic of the system is derived using the Newton-Euler formulation. An unshaped bang-bang force input is used to determine the characteristic parameters of the system for design and evaluation of the feed-forward control techniques. Feed-forwards control schemes based on input shaping and filtering techniques are to be examined. The proposed techniques are designed based on the properties of the system for pitch angle control. Simulation result of the response of unmanned underwater vehicle system to the shaped input are presented in time and frequency domains. Performance of the control schemes are examined in terms of pitch angle reduction and time response specifications. Moreover, the robustness of the feed-forward control schemes is discussed. Finally, a comparative assessment of the proposed control techniques is presented and discussed.